PENGARUH IKLAN ONLINE DAN KUALITAS LAYANAN TOKOPEDIA.COM TERHADAP CITRA MEREK PADA MASYARAKAT KOTA PADANG - Donny Rizbi (Universitas Negeri Padang, 2019)
This study aims to measure online advertising and tokopedia.com service quality on brand image. The population of this study is the people of Padang city who have done shopping at the online store tokopedia.com. Sampling of this study using accidental sampling technique. The number of respondents in this study were 100 respondents. The data collection technique of this study was to use a questionnaire with data analysis, namely using multiple regression analysis. The results of this study indicate tocopedia.com online advertising, a positive and significant effect on brand image and tokopedia.com service quality has a positive and significant impact on brand image.Keywords: online advertising, service quality, brand image